2023
DOI: 10.3389/fmed.2023.1185284
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures associated with chronic endometritis revealed by RNA sequencing

Abstract: IntroductionChronic endometritis (CE) is a persistent inflammatory condition of the endometrium characterized by the infiltration of plasma cells in the endometrial stroma. CD138 immunohistochemistry is considered to improve the CE diagnosis rate.MethodsUsing the number of CD138-positive cells equal or greater than five as a diagnostic criterion for CE, we identified 24 CE and 33 non-CE cases among women with infertility. We conducted RNA-sequencing analysis for these 57 cases in total as an attempt to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Studies have revealed that CD-138+ cells, particularly in the proliferative-phase endometrium, may be an adverse indicator for pregnancy outcomes in in vitro fertilization (IVF) cycles. Elevated counts of CD-138+ cells in the endometrium have been linked to pregnancy failure and are proposed to possess a specific predictive value for pregnancy outcomes [ 15 , 16 ]. Moreover, CD-138 immunohistochemistry has been employed to enhance the diagnostic accuracy of CE.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that CD-138+ cells, particularly in the proliferative-phase endometrium, may be an adverse indicator for pregnancy outcomes in in vitro fertilization (IVF) cycles. Elevated counts of CD-138+ cells in the endometrium have been linked to pregnancy failure and are proposed to possess a specific predictive value for pregnancy outcomes [ 15 , 16 ]. Moreover, CD-138 immunohistochemistry has been employed to enhance the diagnostic accuracy of CE.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, CD-138 immunohistochemistry has been employed to enhance the diagnostic accuracy of CE. Research indicates that the quantification of CD-138-positive cells can be a reliable method for CE detection, with a diagnostic criterion of five or more CD-138+ cells per high-power field (HPF) [ 4 , 8 , 9 , 15 ].…”
Section: Reviewmentioning
confidence: 99%